Electrochemical characterization of redox activity and stability of various tris(2,2‘-bipyridine) derived complexes of iron(II) in aqueous solutions - Hannonen Jenna; Kiesilä Anniina; Mattinen Ulriika; Pihko Petri M.; Peljo Pekka (Elsevier BV, 2025)
Tris(2,2'-bipyridine) Fe(II) complexes with different 4,4'-placed substituents were studied electrochemically in aqueous solutions. Digital simulation of the experimental cyclic voltammograms enabled the evaluation of the redox potentials, electrochemical kinetics as well as complex stability. The substituent effect on the formal potential of the complexes was investigated, showing that electron-withdrawing substituents shift the formal potential to a positive direction from the potential of the unsubstituted [Fe(II)(bpy)3]2+ complex (0.875 V vs. Ag/AgCl). Respectively electron-donating substituents shift the formal potential to a negative direction. The most positive formal potential (0.97 V vs. Ag/AgCl) was obtained with 4,4'-dicarboxyl substituted and the lowest 0.56 V vs. Ag/AgCl with 4,4'-di-OMe substituted [Fe(II)(bpy)3]2+. We show here that the stability of the compounds in the oxidized form can be evaluated by voltammetry. None of the studied complexes was stable enough for flow battery applications, but knowledge of their decomposition rates was obtained via simulations, considering that all oxidized species undergo a chemical reaction, resulting in a loss of redox-active species. The counterion of the complex affected the solubility and stability of the complex, as the presence of tetrafluoroborate resulted in faster decomposition than the presence of sulfate. Battery testing of the most stable Fe(II) complex revealed a voltage drop upon discharge, lowering the energy efficiency. Battery cycling showed a capacity decay most likely related to the chemical reaction occurring to the oxidized species. Even though the studied complexes are not suitable for aqueous flow battery applications as such, knowledge of a substituent, counterion, and electrolyte effect on their performance is needed to develop these complexes further and to improve their stability via structural design. We show here that voltammetry is a suitable tool for fast initial evaluation of the stability of the materials.